A Flexible Architecture for Context-Aware Physical Hypermedia - Challiol, Cecilia (2007)
In this paper we present the rationale and the main components for a modular and extensible architecture for building and deploying physical hypermedia software. We show that this kind of software systems poses strong requirements on supporting software (such as Web browsers) because they involve complex context-aware navigation semantics. By using some simple archetypical examples we also show how to provide context-aware assistance to the mobile user, as he explores the physical world.